Cognitive impairment in the first year after breast cancer diagnosis: A prospective cohort study. (April 2017) - Ramalho, Mariana; Fontes, Filipa; Ruano, Luís; Pereira, Susana; Lunet, Nuno
Abstract: Objectives: The objective of this study was to assess the relation between cancer treatments and incident cognitive impairment in breast cancer patients, taking into account the levels of anxiety before treatment. Materials and methods: We conducted a prospective cohort study with 418 newly diagnosed breast cancer patients with no cognitive impairment, defined as values at least 1.5 standard deviations below age- and education-adjusted cut-offs in the Montreal Cognitive Assessment (MoCA), at baseline. The Hospital Anxiety and Depression Scale and MoCA were used for evaluations before treatment and at 1-year after diagnosis. We used Poisson regressions to compute adjusted relative risks (RR) and corresponding 95% confidence intervals (95%CI) to identify predictors of cognitive impairment. Results: The median (Percentile 25, Percentile 75) MoCA score before treatment was 24 (21, 26). A total of 8.1% (95%CI: 5.8, 11.2) of the patients presented incident cognitive impairment during the follow-up. There was a statistically significant interaction between anxiety at baseline and the effect of chemotherapy on the incidence of cognitive impairment (P for interaction = 0.028). There was a significantly increased risk of incident cognitive impairment among patients with no anxiety prior to treatment with schemes including doxorubicin and cyclophosphamide (adjusted RR = 4.22, 95%CI: 1.22, 14.65). Conclusion: There was a statistically significant association between chemotherapy and cognitive impairment, but only among women with no anxiety at baseline. Highlights: A total of 8.1% of the patients presented cognitive impairment 1-year after diagnosis. The effect of chemotherapy on cognitive impairment depended on levels of anxiety. Risk of cognitive impairment was higher for doxorubicin + cyclophosphamide schemes.